No major association between TGFBR1*6A and prostate cancer - Kaklamani, Virginia (BioMed Central, 2004)
Prostate cancer is the most commonly diagnosed cancer in men and one of the leading causes of cancer deaths. There is strong genetic evidence indicating that a large proportion of prostate cancers are caused by heritable factors but the search for prostate cancer susceptibility genes has thus far remained elusive. TGFBR1*6A, a common hypomorphic variant of the type I Transforming Growth Factor Beta receptor, is emerging as a tumor susceptibility allele that predisposes to the development of breast, colon and ovarian cancer. The association with prostate cancer has not yet been explored. A total of 907 cases and controls from New York City were genotyped to test the hypothesis that TGFBR1*6A may contribute to the development of prostate cancer. TGFBR1*6A allelic frequency among cases (0.086) was slightly higher than among controls (0.080) but the differences in TGFBR1*6A genotype distribution between cases and controls did not reach statistical significance (p = 0.67). Our data suggest that TGFBR1*6A does not contribute to the development of prostate cancer.